Procedimento para avaliação da qualidade do serviço de transporte fretado de funcionários por ônibus sob a ótica do usuário, empresa contratante e prestadora do serviço - Perini, Noéle Bissoli (2015)
The objective of this research is to propose a procedure for assessing the quality of charter bus service and to establish a correlation between the diferent perspectives from passengers, service contractor and service provider. Therefore, the literature review of the main models used to assess the quality of passenger transport services, highlighting their methods, the type of measurement, the views used and the area of application of the models is presented, and presents the attributes and characteristics that influence the quality of passenger transport by bus. Features of this service could be identified and classified on the following attributes: accessibility; travel time; stocking; reliability; security; vehicle characteristics; information systems; connectivity and behavior of operators. Thus, it was possible to propose a procedure for this research. Initially, the deployment characteristics of passenger service raised in the literature on quality requirements for the carriage of passengers by chartering is done. After an analysis of the quality GAPs was held, that is, identified the differences of perceptions of passenger transport quality for each identified feature. For the proposed method, it conducted a field experiment that exposed the characteristics and perceptions of users, the contracting company and provider of employee shuttle service as well as an assessment of the quality of freight transport service employees was carried out .This procedure innovates by including the vision of the service provider as a third agent in the model. Also innovates to deploy the agent "customer" in users and contract managers and also the contractor for drivers and administrative staff. As a result of these innovations, the GAPs were redesigned and rearranged in the proposed procedure.